KLASIFIKASI GEOMORFOLOGI UNTUK PEMETAAN GEOLOGI YANG TELAH DIBAKUKAN - -, Ike Bermana (Bulletin of Scientific Contribution, 2006)
Some expert mention that surface of recent earth is reflection of geological process that goes on at past. Some state in Europe are connecting study of geomophology with geography. It is known as physical geography, but some of state in Europe and America are includes geomophology as geological science branch. While in Indonesia, more uppermost as physical geography, because indirect corellation to activity of development, specially development of agriculture and urban.